On the Non-commutative Neutrix Product of the Distributions $δ ^{(r)}(x)$ and $x^{-s}\ln^m|x|$} - Fisher, Brian; Ege, Inci; Özçag, Emin (Sarajevo Journal of Mathematics, 2024)
It is proved that the non-commutative neutrix product of the distributions $ δ ^{(r)}(x)$ and $x^{-s} \ln^m|x|$ exists and $$ δ ^{(r)}(x) ° x^{-s} \ln^m |x| = 0 $$ for $r,m=0,1,2, …$ and $s = 1,2, ….$ 2000 Mathematics Subject Classification. 46F10